Prevalence and morphological and molecular characteristics of Sarcocystis bertrami in horses in China - Ma Chun-Li; Ye Yu-Long; Wen Tao; Huang Zhu-Mei; Pan Jing; Hu Jun-Jie; Tao Jian-Ping; Song Jing-Ling (Parasite, 2020)
Three cyst-forming Sarcocystis species have been identified in horsemeat; however, there exists considerable confusion concerning their relationships. Here, 74% (34/46) of the examined tissue samples from horses contained sarcocysts based on examination by light microscopy (LM), and the organism was identified as Sarcocystis bertrami based on cyst structure. The S. bertrami cysts were microscopic (up to 6750 μm in length) and exhibited a striated wall with 2.0–5.1 μm villar protrusions (vps) under LM. Transmission electron microscopy (TEM) observations showed that the vps were tightly packed, similar to “type 11c”. Four genetic markers (18S, 28S, ITS1 and the mitochondrial cox1 gene) of S. bertrami were sequenced and analyzed. The 28S and ITS1 sequences are the first records for Sarcocystis in horses. The newly obtained sequences of the 18S and cox1 genes both shared the highest similarities with those of S. bertrami and S. fayeri obtained from horses. Phylogenetic analysis based on the 18S, 28S and cox1 sequences revealed that S. bertrami and S. fayeri formed an independent clade within a group comprising Sarcocystis spp. from ruminants and pigs. Therefore, S. bertrami and S. fayeri are considered to represent the same species of Sarcocystis in horses, and S. fayeri is a junior synonym of Sarcocystis bertrami.